Development of Online Student Olympiad Training Materials for Elementary School Teachers in Magersari Mojokerto Subdistrict in the COVID-19 Pandemic Era - Manuharawati; Raden Sulaiman; Hery Tri Sutanto; Muhammad Jakfar; Toni Phibeta (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
In March 2020, the World Health Organization (WHO) declared COVID-19 as an international pandemic. This condition definitely affects the learning process, especially Mathematics learning in elementary school, and one of the goals expressed by Badan Standar Nasional Pendidikan (BSNP), namely that students have the ability to understand concepts, reason, solve problems, communicate ideas, and have an attitude of appreciating the usefulness of mathematics in life. Most elementary school teachers in Magersari District have not been able to do problem solving training for students and they need help to improve their abilities in assisting their students in solving Math Olympiad problems. Therefore, an activity was held to development of online student olympiad training materials for elementary school teachers in Magersari Mojokerto Subdistrict. Base on the evaluation, it can be concluded that this activity can improve the ability of teachers to develop Math Olympiad questions at the elementary school level and be able to solve them with problem solving steps; In solving problems related to integers, teachers can apply the properties of integer operations, and do not use formulas that are not familiar to elementary school children; And also, this activity is felt to be fun and in accordance with its objectives.